Single-cell mass cytometry and transcriptome profiling reveal the impact of graphene on human immune cells. Issue 1 (December 2017) - Orecchioni, Marco; Bedognetti, Davide; Newman, Leon; Fuoco, Claudia; Spada, Filomena; Hendrickx, Wouter; Marincola, Francesco; Sgarrella, Francesco; Rodrigues, Artur Filipe; Ménard-Moyon, Cécilia; Cesareni, Gianni; Kostarelos, Kostas; et al.
Abstract Understanding the biomolecular interactions between graphene and human immune cells is a prerequisite for its utilization as a diagnostic or therapeutic tool. To characterize the complex interactions between graphene and immune cells, we propose an integrative analytical pipeline encompassing the evaluation of molecular and cellular parameters. Herein, we use single-cell mass cytometry to dissect the effects of graphene oxide (GO) and GO functionalized with amino groups (GONH2 ) on 15 immune cell populations, interrogating 30 markers at the single-cell level. Next, the integration of single-cell mass cytometry with genome-wide transcriptome analysis shows that the amine groups reduce the perturbations caused by GO on cell metabolism and increase biocompatibility. Moreover, GONH2 polarizes T-cell and monocyte activation toward a T helper-1/M1 immune response. This study describes an innovative approach for the analysis of the effects of nanomaterials on distinct immune cells, laying the foundation for the incorporation of single-cell mass cytometry on the experimental pipeline. Understanding the interaction of nanomaterials and immune cells ﻿at the biomolecular level is of great significance in therapeutic applications. Here, the authors investigated the interaction of graphene oxide nanomaterials and several immune cell﻿ subpopulations using single-cell mass cytometry and genome-wide transcriptome analysis.